Rewarding conservative politicians? Evidence from voting on same-sex marriage - Björn Kauder; Niklas Potrafke (Public Choice, 2022)
We ask whether voters rewarded conservative politicians who voted in favor of same-sex marriage. The evidence is based on a rollcall vote in the German national parliament (Bundestag) in June 2017. That vote had a profound influence on public discourse concerning the social-political platforms of the conservative parties in Germany, the Christian Democratic Union (CDU) and its Bavarian sister party Christian Social Union (CSU). National elections took place in September 2017. We find that, when comparing the outcomes of the 2017 and 2013 national elections, the vote share of conservative politicians who voted in favor of same-sex marriage was around 1.29% points higher (about 0.33 standard deviations of the change in the candidate's vote share) than the vote share of conservative politicians who did not vote in favor of same-sex marriage. Voters apparently were seeking policy outcomes other than economic ones when evaluating politicians' performances in office.
Keywords: D72; D78; P16; 330; Rewarding and punishing politicians; Conservative politicians; Rollcall votes; Same-sex marriage; Economic voting